Mining spatial association rules in image databases - Lee, Anthony J.T.; Hong, Ruey-Wen; Ko, Wei-Min; Tsao, Wen-Kwang; Lin, Hsiu-Hui (Information sciences, 2007)
In this paper, we propose a novel spatial mining algorithm, called 9DLT-Miner, to mine the spatial association rules from an image database, where every image is represented by the 9DLT representation. The proposed method consists of two phases. First, we find all frequent patterns of length one. Next, we use frequent k-patterns ( k ⩾ 1) to generate all candidate ( k + 1)-patterns. For each candidate pattern generated, we scan the database to count the pattern’s support and check if it is frequent. The steps in the second phase are repeated until no more frequent patterns can be found. Since our proposed algorithm prunes most of impossible candidates, it is more efficient than the Apriori algorithm. The experiment results show that 9DLT-Miner runs 2–5 times faster than the Apriori algorithm.